Analysis of physical and mechanical soil properties determined using probing data interpretations - Virsis, Endijs; Paeglitis, Ainars (International Conference “Environmental Engineering”, 2023)
Road design is a complex, time-consuming, and very responsible process. To develop a high-quality and viable road project, it is very important to start with an accurate geological investigation. In situ tests can provide a number of advantages over the traditional drilling, sampling and laboratory testing approach used in many geotechnical projects. However, like all tests, in situ tests also have a number of limitations. Although all probing methods are similar, each of them gives slightly different results. The aim of this work was to analyse and compare the interpretation results of soil layer physical-mechanical properties obtained with different in-situ test methods and to find out how the obtained results affect the development of constructive solutions from the safety point of view.